Designing and Implementing HOTS-Oriented Learning by Mathematic Teachers - Chiarun Nisa, Nenden; Mulyaning, Endang Cahya (International Journal of Contemporary Studies in Education, 2022)
Higher-Order Thinking is a skill to be achieved to face the 21st century. Some previous research shows HOTS-oriented learning can improve students' higher-order thinking skills. This research aims to analyze the plan and implementation of HOTS-oriented learning by mathematics teachers. This research is a phenomenological research with a qualitative approach with the subject of 20 mathematics teachers in junior high schools who have attended the training. The teachers designed the lesson plan, implemented it in their school and then the FGDs are conducted to find out the experiences of each teacher. Research shows that mathematics teachers have tried to do HOTS-oriented learning, but still have many obstacles and difficulties in its implementation. Thus, HOTS learning must be done continuously to make students accustomed to doing HOTS-oriented learning activities.